Antiracist Medievalisms From "Yellow Peril" to Black Lives Matter - Hsy, Jonathan (Arc Medievalist, 2022)
How do marginalized communities across the globe use the medieval past to combat racism, educate the public, and create a just world? Jonathan Hsy advances urgent academic and public conversations about race and appropriations of the medieval past in popular culture and the arts. Examining poetry, fiction, journalism, and performances, Hsy shows how cultural icons such as Frederick Douglass, Wong Chin Foo, Alice Dunbar-Nelson, and Sui Sin Far reinvented medieval traditions to promote social change. Contemporary Asian, Black, Indigenous, Latinx, and multiracial artists embrace diverse pasts to build better futures. "Makes the crucial move of tying medievalism studies readings to social and racial justice work explicitly ... innovative and greatly needed in the field." Seeta Chaganti, author of Strange Footing "A major accomplishment that belongs on the shelves of every person who believes in antiracism." Geraldine Heng, author of The Invention of Race in the European Middle Ages